Identification of Maleo (Macrocephalon Maleo) and Gosong Kaki Merah (Megapodius Reindwardt) DNA Similarity Level Using Needleman-Wunsch Algorithm - Rusmi, Rusmi; Ratianingsih, Rina; Najar, Abdul Mahatir (Transcendent Journal of Mathematics and Applications, 2023)
Sequence Alignment is used to find out the similarity of the sequence of two DNA. One of the alignment algorithms is the Needleman-Wunsch algorithm which is a global alignment algorithm that uses the entire length of the DNA sequence. In this research, the algorithm is applied to a website-based application system to determine the level of similarity of the DNA sequence of Maleo (Macrocephalon Maleo) which is an endemic animal to Sulawesi, with a comparison of Gosong Kaki Merah (Megapodius Reinwardt) which has a wide global distribution. The results of the alignment of Maleo (Macrocephalon Maleo) and Kaki Merah (Megapodius Reinwardt) DNA sequences on a website-based application system have an average similarity level of 83.39% and an average gap value of 8.42%.